THE INTERDISCIPLINAR EDUCATION CENTER (CENTRO DE FORMAÇÃO INTERDISCIPLINAR) - Nascimento, Paiva, Roberto Do (European Scientific Journal, ESJ, 2013)
At the federal university of western pará - ufopa, brazil, the center for interdisciplinary education - cfi and the interdisciplinary education 1, at which students acquire during their first academic period, a general training of multi and interdisciplinary nature that meets knowledge to the world of reality reflected through the local reality. It is academic and citizenship offered by specific instance. Regarding the interdisciplinary training 1 - first component of the first general cycle interdisciplinary undergraduate - is based on knowledge articulated through five interdisciplinary modules, for which it produced a collection of modular books namely: logic, languages and communication - llc; origin and evolution of knowledge - oec; society, nature and development - snd; amazon integrative studies – eia, integratives seminars with interaction with a real base, sint / ibr. Through reading and studying these modules interdisciplinary students come into contact with a range of information, content and concepts that will guide their understanding of the amazon region of brazil and the world and establish a research and a scientific exploration to present in internal academic conference at oral communication and banners; since then the student may choose an academic course that will determine his entire professional career.